Comparison of Shear Bond Strengths of Ceramic Brackets Using Either Self-etching Primer or Conventional Method After Intracoronal Bleaching - Fethiye Cakmak; Sibel Kocak; Mustafa Murat Kocak; Selma Elekdag-Turk; Tamer Turk (Galenos Yayinevi, 2015)
Objective:To evaluate initial shear bond strengths (SBSs) of ceramic brackets using either a self-etching primer (SEP) or the conventional method (CM) after intracoronal bleaching with sodium perborate and distilled water.Materials and Method:Eighty human incisors were divided into 4 groups according to bleaching and bonding procedures: group 1, bleaching was not applied and brackets were bonded with SEP; group 2, bleaching was not applied and brackets were bonded with the CM; group 3, intracoronal bleaching with sodium perborate was applied for 3 weeks and brackets were bonded with SEP; group 4, intracoronal bleaching with sodium perborate was applied for 3 weeks and brackets were bonded with the CM. The SEP (Transbond Plus) was applied as recommended by the manufacturer. After SEP application, ceramic brackets were bonded with light cure adhesive (Transbond XT). For the CM, the teeth were etched with 37% phosphoric acid. After etching, a thin uniform coat of primer (Transbond XT Primer) was applied and ceramic brackets were bonded with light cure adhesive (Transbond XT). The SBSs were measured after water storage for 30 days, after 1000 cycles of thermocycling between 58C and 558C. Bond failure location was determined with the adhesive remnant index (ARI).Results:For the SEP method, there was no significant difference between the SBS values of the bleaching and nonbleaching groups. Furthermore, for the CM, the SBS value of the nonbleaching group was not significantly different from that of the bleaching group. The SBS values of the SEP method presented significant differences from the SBS values of the CM (p , 0.001). The SBS values of the SEP application decreased with and without bleaching. ARI scores did not show any significant difference between the groups (p = 0.174).Conclusion:Intracoronal bleaching with sodium perborate and distilled water did not affect the SBS values of ceramic brackets.